Acessibilidade e segregação em vias urbanas: análise da caminhabilidade, nas calçadas dos distritos Jardim Ângela e Moema, município de São Paulo/ SP - Brasil - Calado, Jane da Cunha (2019)
The Brazilian urbanization process, characterized by being late and accelerated, resulted in a state of urban crisis, reflected in several challenges, among them the deep socio-spatial segregation. Such segregation is also present in the difficulties of mobility and access of a large part of the population to the services and opportunities offered in urban space. The problems of accessibility and the reduced concern with attending to universal design in the public spaces of the city of São Paulo can be observed by the rudimentary conditions of the sidewalks, which hinder the social integration, especially of people with disabilities and the elderly population. In spite of the importance of the theme, there is a lack of work in the literature on the diagnosis of traffic conditions and the level of service of sidewalks in the city of São Paulo and to understand their relationship with existing socio-spatial inequalities. In this sense, the present project had the objective of diagnosing degrees of accessibility in sidewalks, as well as the relation of these with the socio - spatial inequalities in the city of. The research is classified as exploratory and was based on bibliographic survey, remote sensing techniques and field activities. As a study area, we adopted the Districts that presented the highest and lowest Index of Social Vulnerability and Household Income, according to data from the 2010 Demographic Census, being, respectively, Jardim Ângela and Moema. In order to evaluate the accessibility condition of the District, a spatial cut-out was performed, based on circular samples and maintaining a covering of at least 30% of the study area. Afterwards, a diagnosis of the accessibility indices of sidewalks and crossings [IACT] was carried out, applied to the interior of the samples. The results presented allowed the observation of the accessibility and mobility conditions of the selected sidewalks, as well as the identification of relationships between their accessibility conditions and existing sociospatial inequalities.